1990
DOI: 10.1111/j.1365-3083.1990.tb03200.x
|View full text |Cite
|
Sign up to set email alerts
|

Tγδ Cells and their Subsets in Blood and Synovial Tissue from Rheumatoid Arthritis Patients

Abstract: We have examined the frequencies of T gamma delta cells in blood, synovial fluids, and synovial membranes of patients with rheumatoid arthritis (RA) and in blood from age-matched controls. Immunocytochemical and immunohistochemical techniques were used with monoclonal antibodies BB3 and A13 to define a major and minor blood subset of T gamma delta cells respectively. Together, these antibodies identify the majority (if not all) of the peripheral blood T gamma delta cells. Significantly lower levels of T gamma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
32
1

Year Published

1992
1992
1998
1998

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(35 citation statements)
references
References 43 publications
2
32
1
Order By: Relevance
“…We have previously shown that the majority of synovial yd T cells in JRA patients express the Vi51J51/2 gene products, whereas only a minor proportion uses the Vdl gene segment [2]. Similar results have also been reported in RA [3][4][5][6][7]. In JRA patients we also detected H LA-DR and the very early activation antigen CD69 [23] on synovial yd T cells.…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…We have previously shown that the majority of synovial yd T cells in JRA patients express the Vi51J51/2 gene products, whereas only a minor proportion uses the Vdl gene segment [2]. Similar results have also been reported in RA [3][4][5][6][7]. In JRA patients we also detected H LA-DR and the very early activation antigen CD69 [23] on synovial yd T cells.…”
Section: Introductionsupporting
confidence: 86%
“…Most of these eells express the a/i T cell receptor whereas a small proportion (5-15%) express the yd T cell receptor. It is established that the afi T cells recognize antigen in context with MHC class I or class II molecules, but for the yd T cells little is known eoneerning expression of activation markers, activation requirements, antigenic repertoire and restriction elements used, yd T cells have been studied in a number of pathological conditions such as RA and JRA [2][3][4][5][6][7], leprosy [8], polymyositis [9], eoeliac disease [10][11], eancer [12][13][14], primary immunodeficiency syndrome [15,16], Behijet's disease [17], and infections with Epstein-Barr virus [18] and HIV-1 [19]. Promiscuous cytotoxicity exerted by yd T cells has been documented in vitro [20,21] Correspondence: Dr Jens Kjeldsen-Kragh, Red Cross and National Hospital Blood Centre, PO Box 6739, St Olavs Plass, N-0130 Oslo, Norway.…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that, in addition to the small bowel mucosa in patients with celiac disease, Val + T cells are enriched in the synovial membrane and synovial fluid in rheumatoid arthritis (36,37). According to a recent study, these cells could play a significant role in the destruction of joints in rheumatoid arthritis, since they may be directly cytotoxic to the cells that comprise the joint structure (38).…”
Section: Discussionmentioning
confidence: 99%
“…Tbe elevation of A13+ y6J cells in patients witb AI-CAH or PSC suggests that Cy2/56\/'V6\ genes may bave undergone rearrangement. It has been described that this subtype of yS'*' T cells is over-represented in the peripheral blood, synovial membrane and synovial fluid of patients with rheumatoid arthritis [5,15], in the gastrointestinal tract of patients with coeliac disease [15][16][17] and also in the peripheral blood of patients with common variable immunodeficiency or patients infected witb HIV [18][19][20]. These findings may suggest that activation of tbis subset of y^+ T cells characteristically occurs in response to both endogenous stimuli, such as autoantigens, and exogenous, sucb as viruses or bacteria.…”
Section: Discussionmentioning
confidence: 99%